Social change through diffusion of sustainability innovations from the bottom-up - Ortiz Orozco, Willington (Medien- und Informationszentrum, Leuphana Universität Lüneburg, 2019)
"Sustainable development" evolves along the resolutions, declarations, and reports from international processes in the framework of the United Nations (UN). The consensual outputs from such processes feature global-generalised and context-free perspectives. However, implementation requires action at diverse and context-rich local levels as well. Moreover, while in such UN processes national states are the only contractual parties, it is increasingly recognised that other ("nonstate") actors are crucial to sustainability. The research presented here places the attention on bottom-up initiatives that are advancing innovative ways to tackle universal access to clean energy and to strengthen small-scale family farmers. This means, the focus is on bottom-up initiatives advancing local implementation of global sustainability targets, more precisely, targets that make part of the Sustainable Development Goals 2 and 7 (SDG 2 and SDG7). The research asks how such bottom-up initiatives can contribute to the diffusion of sustainability innovations, thereby also contributing to social change. Three aims are derived out of that central question: (1) To understand the role of bottom-up initiatives in the diffusion of sustainability innovations and in the thereby involved social changes. (2) To contribute with my research to the actual diffusion of sustainability innovations. (3) To outline a research approach that provides a solid conceptual and methodological framework for attaining the analytical and transformative aims. The doctoral research comprises four single studies, in which the notion of diffusion is explored at different scopes of social scales. It begins with a thorough analysis of diffusion programs of domestic biodigesters to rural households in countries of the global south. The focus is on the process by which this specific technical inno0vation results integrated (or not) into the daily realities of single rural households, that is, the adoption process. In the second study, the attention is on energy supply models based on different decentralised renewable technologies. Central to these models is the building of new (or strengthening of existing) local socioeconomic structures that can assume and ensure the proper operation and supply of energy services. The interest in this study is on the strategies that organisations implementing community-based energy projects apply to support the realisation of such local structures. The third study focuses on a network of bottom-up initiatives that have been advancing alternative approaches to family farming in Colombia. The network mainly comprises farmers associations, other organisations from civil society, and researchers who had been collaborating and experimenting with innovations in different innovation fields such as technical, organisational, financial, and commercialisation schemes. The aim of this third study is to provide insights into the challenges and difficulties faced by these actors in broadening the diffusion of the innovations they have been advancing. To perform this study, a methodological strategy is applied that combines a transdisciplinary mutual learning format with qualitative content analysis techniques. The fourth and last study is a conceptual disquisition. It develops a conceptual framework that (a) provides better accounts for the particularities of endeavours aimed at the diffusion of knowledge and practices from the bottom-up across local contexts and social scales, and (b) advances first conceptual steps towards an explicit account for the role that innovation research (and innovation researchers) can assume for the actual realisation of diffusion. The main findings or contributions of the doctoral research can be categorised into four subjects: 1) Bottom-up initiatives contribute to the diffusion of sustainable innovations by mobilising transformative resources for inducing diffusion in their scope of action and creating spaces for experimentation in which interventions can be tested (and if necessary adjusted) in order to ensure the proper deployment of innovations. 2) In their efforts to advance the diffusion of sustainability innovations, bottom-up initiatives contribute to social changes for ensuring the effective deployment of the innovations and building local available storage of transformative resources. 3) A conceptualisation of innovation diffusion, in which the work of academic researchers studying innovation is a constitutive part of transdisciplinary knowledge articulations that promote diffusion. In this way transdisciplinary research alliances can be envisioned in which researchers investigate about, with, and for bottom-up initiatives. 4) Contributions to the consolidation, systematisation, and dissemination of strategies that are applied by farmers associations in order to strength the economic, social, environmental, and cultural dimensions of Colombian family farmers.

Der Begriff "Nachhaltige Entwicklung" lässt sich entlang der Resolutionen, Erklärungen und Berichte aus internationalen Prozessen im Rahmen der Vereinten Nationen (UN) verfolgen. Die auf Konsens basierten Ergebnisse solcher Prozesse weisen eine global verallgemeinernde und kontext-freie Perspektive auf. Die praktische Umsetzung erfordert jedoch auch Handlungen auf verschiedenartigen und kontext-reichen lokalen Ebenen. Auch wenn in solchen UN-Prozessen nur Nationalstaaten als unterzeichnende Parteien gelten, wird zunehmend anerkannt, dass andere ("nonstate") Akteure für die Debatten und die Umsetzung von Nachhaltigkeit entscheidend sind. Die hier vorgestellte Forschung beschäftigt sich mit Bottom-up-Initiativen, die innovative Wege zur Sicherung des Zugangs zu bezahlbarer, verlässlicher, nachhaltiger Energie für alle und zur Stärkung kleiner Familiy Farmers fördern. Der Fokus liegt also auf Bottom-up-Initiativen, die die lokale Umsetzung globaler Nachhaltigkeitsvorgaben vorantreiben, genauer gesagt, auf Vorgaben, die Teil globaler Ziele für nachhaltige Entwicklung (Sustainable Development Goals) 2 und 7 sind (SDG2 und SDG7). Die Forschung fragt, wie solche Bottom-up-Initiativen zur Verbreitung von Nachhaltigkeitsinnovationen und damit auch zum sozialen Wandel beitragen können. Aus dieser zentralen Frage leiten sich drei Forschungsziele ab: (1) Die Rolle von Bottom-up-Initiativen bei der Verbreitung von Nachhaltigkeitsinnovationen und den damit verbundenen sozialen Veränderungen zu verstehen. (2) Einen Beitrag zur tatsächlichen Verbreitung von Nachhaltigkeitsinnovationen zu leisten. (3) Einen Forschungsansatz zu skizzieren, der einen soliden konzeptionellen und methodischen Rahmen für die Erreichung der analytischen und transformativen Ziele bietet. Die Forschung umfasst vier Einzelstudien, in denen der Begriff der Diffusion auf verschiedenen sozialen Skalen untersucht wird. Es beginnt mit einer gründlichen Analyse der Diffusionsprogramme von Kleinstbiogasanlagen in ländlichen Regionen in Ländern des globalen Südens. Im Mittelpunkt steht der Adoptionsprozess, d.h. wie die spezifischen Innovation in die tägliche Realität einzelner Haushalte integriert wird (oder nicht). In der zweiten Studie geht es um Energieversorgungsmodelle, die auf verschiedenen dezentralen erneuerbaren Technologien basieren. Im Mittelpunkt dieser Modelle steht der Aufbau neuer (oder die Stärkung bestehender) lokaler sozioökonomischer Strukturen, die den ordnungsgemäßen Betrieb der technischen Innovationen und die Bereitstellung von Energiedienstleistungen übernehmen und sicherstellen können. Das Interesse dieser Studie liegt auf den Strategien der durchführenden Organisationen, um durch die Implementierung gemeindebasierte Energieprojekte die Realisierung solch lokaler Strukturen zu unterstützen. Die dritte Studie konzentriert sich auf ein Netzwerk von Bottom-up-Initiativen, die alternative Ansätze für Family Farmers in Kolumbien entwickeln. Das Netzwerk besteht hauptsächlich aus Kleinbauernverbänden, anderen Organisationen der Zivilgesellschaft und Forschern, die mit Innovationen in verschiedenen Innovationsfeldern wie technischen, organisatorischen, finanziellen und kommerziellen Maßnahmen zusammenarbeiten. Ziel dieser dritten Studie ist es, die Herausforderungen und Schwierigkeiten dieser Akteure bei der Diffusion der von ihnen vorangetriebenen Innovationen zu erforschen. Um diese Studie durchzuführen, wird eine methodische Strategie angewandt, die ein transdisziplinäres gegenseitiges Lernformat mit qualitativen Inhaltsanalyseverfahren kombiniert. Die vierte Studie ist eine konzeptionelle Abhandlung. Sie entwickelt einen konzeptionellen Rahmen, der (a) die Besonderheiten der Diffusion von Wissen und Praktiken von Bottom-up-Initiativen jenseits ihrer lokalen Kontexte berücksichtigt und (b) erste konzeptionelle Schritte in Richtung einer expliziten Berücksichtigung der Rolle, die die Innovationsforschung für die tatsächliche Realisierung von Diffusion einnehmen kann, vorantreibt. Die Hauptergebnisse oder Beiträge der Forschung lassen sich in vier Bereiche unterteilen: 1) Bottom-up-Initiativen tragen zur Verbreitung nachhaltiger Innovationen bei durch: die Mobilisierung transformativer Ressourcen und die Schaffung von Experimentierräumen, in denen Interventionen getestet (und gegebenenfalls angepasst) werden können. 2) In ihren Bemühungen, die Verbreitung von Nachhaltigkeitsinnovationen voranzutreiben, tragen Bottom-up-Initiativen zu sozialen Veränderungen bei, die den effektiven Einsatz der Innovationen sicherstellen und den lokal verfügbaren "Storage" transformativer Ressourcen aufbauen. 3) Die Entwicklung einer Konzeptualisierung von Diffusionsprozesse, bei der die Arbeit von akademischen Innovationsforschern ein konstitutiver Bestandteil transdisziplinärer Wissensartikulationen ist, in denen Innovationsdiffusion gefördert wird. Auf diese Weise lassen sich transdisziplinäre Forschungsallianzen bilden, in denen Forscher über, mit und für Bottom-up-Initiativen forschen. 4) Beiträge zur Konsolidierung, Systematisierung und Verbreitung von Strategien, die von Kleinbauernverbänden angewandt werden, um die wirtschaftliche, soziale, ökologische und kulturelle Dimension der kolumbianischen Family Farmers zu stärken.
Gesellschaftlicher Wandel durch Bottom-up-Innovationsdiffusion: Fallbeispiele in erneuerbaren Energien und nachhaltigen landwirtschaftlichen Praktiken im globalen Süden
Case studies of renewable energy and sustainable farming practices in the global south
Keywords: 630 Landwirtschaft und verwandte Bereiche